Restratification structure and processes in the Irminger Sea - Sterl, M.F.; de Jong, M.F. (Journal of Geophysical Research: Oceans, 2022)
The Irminger Sea is one of the few regions in the ocean where deep (>1,000 m) convection occurs. Convection is followed by restratification during summer, when the stratification of the water column is reestablished and the convectively formed water is exported at depth. There are currently no descriptions of interannual variability and physical drivers of restratification in the Irminger Sea. We investigate restratification in the upper 600 m of the central Irminger Sea using reanalysis data for the years 1993–2019. We find distinctly different restratification processes in the upper 100 m (the upper layer) and the water below it (the lower layer). In the upper layer, the stratification is dominated by a seasonal cycle that matches the cycle of the surface heat flux. In 2010 and 2019, there were peaks in upper layer restratification, which could partly be related to strong atmospheric heat and freshwater fluxes. Greenland runoff likely also contributed to the high restratification, although this contribution could not be quantified in the present study. In the lower layer there is strong interannual variability in stratification, caused by variability both in the convection and the restratification strength. The restratification strength is strongly correlated with the eddy kinetic energy in the eastern Irminger Sea, suggesting that lower layer restratification is driven by lateral advection of warm, saline waters through Irminger Current eddies. In the future, surface warming and freshening of the Irminger Sea due to anthropogenic climate change are expected to increase upper layer stratification, potentially inhibiting convection.